Logic for programming, artificial intelligence, and reasoning : 20th International Conference, LPAR-20 2015, Suva, Fiji, November 24-28, 2015 : proceedings /: 20th International Conference, LPAR-20 2015, Suva, Fiji, November 24-28, 2015 : proceedings. ([2015]) - Unknown
No abstract available